Redução da exposição de risco na mineração com uso de ferramenta IoT - SILVA, Matheus Gama da (2023)
The present work presents a monitoring project applied within the iron mine in Carajás, for the company Vale S.A, carried out with the objective of reducing the time of exposure of the team to risks. To achieve this objective, the ZABBIX monitoring tool was used to collect data from the equipment, through sensors embedded in the equipment and, thus, communicate with the company’s internal network and through the Grafana software can generate dynamic reports. The results obtained indicate a significant reduction in the time spent on inspections of the monitored equipment: Generator, Eltek and Shelter, taking into account the year 2022 that did not have monitoring with the current data until June 2023, when some of the equipment is already in monitored. This project contributes to the area of telecommunication, computer networks and automation by presenting an important application for the industrial segment.